Comparison of healing time and the histopathology of bone formation following tooth extraction using freeze-dried bone allograft:A randomized controlled clinical trial - Omid Moghaddas; Nima Naddafpour; Sareh Farhadi; Peyman Nikookar; Sephora Khandan (Journal of Advanced Periodontology and Implant Dentistry)
Background. A decrease in the width and height of the alveolar ridge is inevitable following tooth extraction. This study aimed to histologically evaluate the amount of newly formed bone after using a freeze-dried bone allograft (FDBA) at two different intervals in the tooth socket grafting. Methods. Forty patients were selected, who required a single-rooted tooth extraction and were candidates for implant placement, with no indication for an immediate implant. Extraction sockets were preserved using a cortical FDBA allograft in two regeneration interval groups: 3 months (group A) and 4 months (group B). At the time of implant placement, a bone sample was collected from each grafted socket. Histomorphometric analyses were performed to determine the percentage of newly formed bone and the residual graft material. Changes in histological indices, i.e., inflammation rate, percentage of ossification, and the amount of remaining biomaterial, were evaluated. Results. There were no significant differences in the amount of newly formed bone and residual graft material between the two groups. In general, the average of new bone formation and remaining graft particles in groups A and B was: %33.89 and %12.59 vs. %39.83 and %14.07, respectively. Conclusion. Bone parameters in group A were better compared to group B. However, due to the lack of significant differences in the results, it is suggested that implant placement in grafted sockets with mineralized allografts be expedited.